Finite element analysis of the heat transfer in a piston - Aisha, Muhammad; Shanono, I. H. (Penerbit UMP, 2020)
The gas expansion process that takes place in a piston cylinder assembly have been used in numerous applications. However, the time-dependent process of heat transfer is still not fully apprehended as the expansion processes are complex and difficult due to the unsteady property of the turbulent flow process. Internal combustion Engines(ICE) designs are conducted with the aim of achieving higher efficiency in the thermal characteristics. To optimize these designs, numerical simulations are conducted. However, modelling of the process in terms of heat transfer and combustion is complex and challenging. For a designer to understand, calculate and quantify the thermal stresses and heat losses at different sections of the structure, understanding the piston-cylinder wall is needed. This study carried out a numerical simulations based on Finite Element Method (FEM) to investigatethe stresses in the piston, and temperature after loading. Appropriate boundary conditions were set on different surfaces for FE model. The study includes the effects of the thermal conductivity of the material of piston, cylinder wall, and connecting rod. Results show the maximum Von-misses stress occurs on the piston head with a value of 3486. 1MPa. The maximum temperature of the piston head and cylinder wall stands at 68.252 and 42.704 degree Celsius respectively.